Handbook of sustainable development - Harlow, Kane (Callisto Reference, 2015)
This book highlights the importance of adopting a sustainable approach to development processes. The technological development of the human civilization has generated a consumer society spreading faster than the resources of Earth allow, with the demands on energy requirements growing exponentially in the last century. Protecting the future of human race requires an improved comprehension of the environment as well as of scientific solutions, behaviors and attitudes in line with the modes of advancement that the ecosphere of Earth can withstand. Certain veterans see this as the only solution in a global deflation of the presently unsustainable exploitation of resources; however, sustainable development presents an approach that would be practical to fuse with the managerial techniques and evaluation tools for policy and decision markers at the regional planning level. Architects, policy makers, environmentalists, engineers and economists will have to work hand in hand for the purpose of ensuring that development and planning can satisfy the current requirements of society without compromising the security of future generations. This book will provide valuable approaches and practical solutions in achieving the targets of sustainable development.